Eros and Modernity: Georg Simmel on Love - Oakes, Guy (Simmel Studies)

(untitled) (Edizioni ETS, 2021)
The text below was originally published under the name “Eros and Modernity: Simmel on Love” in: The Sociology of Emotions: Original Essays and Research Paper. Franks, D.D. and E. Doyle McCarthy (ed.). Greenwich, CT: JAI press, 1989, pp. 229-247. In the words of its author, the text was written at a time when he was intensely engaged with Simmel, working on his philosophy of history and his hermeneutics. Today, Guy Oakes revisits this text and allows Simmel Studies Journal to republish it for this special issue on love. The text explores in its first part the defining characteristics of erotic love according to Simmel: individuality, reciprocity, immediacy and radicalism. In the second part he concentrates on modernity and how it has had an impact on love relationships.